2006
DOI: 10.1248/cpb.54.1425
|View full text |Cite
|
Sign up to set email alerts
|

Cucurbitane Glycosides from Unripe Fruits of Lo Han Kuo (<i>Siraitia grosvenori</i>)

Abstract: Lo Han Kuo is the fruit of the Siraitia grosvenori SWINGLE (formerly Momordica grosvenori SWINGLE) belonging to Cucurbitaceae species and used as a pulmonary demulcent and emollient for the treatment of dry cough, sore throat, dire thirst, and constipation in traditional Chinese medicine.1) Recently, some intriguing pharmacological characteristics such as anti-cancer and anti-hyperglycemic effects, and inhibition of oxidative modification of low density-lipoprotein were reported.2-4) Therefore it was suggested… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
14
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(14 citation statements)
references
References 8 publications
0
14
0
Order By: Relevance
“…1), and the isolation of three known kaempferol glycosides from Cardamine leucantha, kaempferol 7-O-a-l-rhamnopyranoside [5], kaempferitrin [5], and kaempferol 3-O-b-d-galactopyranosyl-7-O-a-l-rhamnopyranoside [5] [6]. All these compounds were reported for the first time from the title plant, and their structures were elucidated based on the combination of 1D-and 2D- ( 1 H-and 13 C-NMR, COSY, HSQC, and HMBC) NMR spectroscopic and mass spectrometric (HR-ESI-MS) techniques.…”
mentioning
confidence: 99%
“…1), and the isolation of three known kaempferol glycosides from Cardamine leucantha, kaempferol 7-O-a-l-rhamnopyranoside [5], kaempferitrin [5], and kaempferol 3-O-b-d-galactopyranosyl-7-O-a-l-rhamnopyranoside [5] [6]. All these compounds were reported for the first time from the title plant, and their structures were elucidated based on the combination of 1D-and 2D- ( 1 H-and 13 C-NMR, COSY, HSQC, and HMBC) NMR spectroscopic and mass spectrometric (HR-ESI-MS) techniques.…”
mentioning
confidence: 99%
“…1), 11) signals ascribable to the aglycone were identical. Moreover, the 13 C-NMR data were analogous with the reported data of cucurbitane triterpenoid.…”
mentioning
confidence: 82%
“…The fruits of Siraitia grosuenorii (Swingle) C. Jeffrey ex A.M. Lu & Zhi Y. Zhang, cultivated in China, are used as a natural sweetening agent and it has been reported to have beneficial effects in the diabetic subjects for its antihyperglycemic role [ 99 ]. Many reports have also shown that it has antitumoral and antioxidant properties [ 100 , 101 ].…”
Section: Herb-derived Products With An Antiaging and Antisenescentmentioning
confidence: 99%